Older, How? The Importance of Practising Educative and Healthy Activities - Carlos Sousa Reis, María José Flores Tena, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to study active ageing by participation in educative and healthy activities (PE&HA) at centres that provide active ageing programmes. An exploratory quantitative study was undertaken, envisaging to explore the relationship between certain variables (age, sex, attendance and type of activity) and the degree of satisfaction with PE&HA. An intentional non-probabilistic sampling was applied to select 800 persons over 55, corresponding to users of various senior centres located in four districts of Madrid, Spain. The data collection instrument consisted of 29 easy-to-understand questions grouped into six dimensions. Results of the questionnaire indicate that users are satisfied with PE&HA offered by the centres. According to 78% of the respondents, the participation in workshops and other group activities contribute to a better quality of life in the elderly, and no statistically significant differences were found between the users’ degree of satisfaction and gender. This research provides possible improvements in areas that will contribute to preventing dependence; for example, those in which there is a greater demand from users. As proposals for improvement, we suggest designing specific strategies to obtain more male participation in senior centre workshops.